2013
DOI: 10.36076/ppj.2013/16/e25
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smokers Have Reduced Risk for PostDural Puncture Headache

Abstract: Background: Although headache is the most common complication of dural puncture, knowledge gaps remain about patient-related risks. Data are lacking on the role, if any, of tobacco smoking, race, anxiety, depression, and Post Traumatic Stress Disorder (PTSD) in conferring risk for post-dural puncture headache (PDPH). Objective: To determine the influence of tobacco smoking, race, anxiety, depressed mood, and PTSD on the risk for PDPH. Study Design: Retrospective chart review, single site. Methods: We determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…In our study, 73,3% of the patients with PDPH were women, but this difference was not statistically significant compared to subjects without a headache (group 2). No correlation between PDPH and BMI was found in our study, which is in agreement with some studies [9,11], but not with others [3,8]. In terms of the LP method, it has been shown that needle type, needle size, operator experience, and procedure technique might all be major factors in the development of PDPH.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, 73,3% of the patients with PDPH were women, but this difference was not statistically significant compared to subjects without a headache (group 2). No correlation between PDPH and BMI was found in our study, which is in agreement with some studies [9,11], but not with others [3,8]. In terms of the LP method, it has been shown that needle type, needle size, operator experience, and procedure technique might all be major factors in the development of PDPH.…”
Section: Discussionsupporting
confidence: 89%
“…Also, it was determined that patients with a history of chronic or recurrent headaches or a recent headache (within the last seven days) before an LP be more likely to report PDPH [8,10]. Interestingly, smokers had a lower incidence of PDPH than on-smokers [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations